Association between serum uric acid and all-cause and cardiovascular-related mortality in hemodialysis patients - Gan, Wenyuan; Zhu, Fan; Fang, Xun; Wang, Wenzhe; Shao, Danni; Mao, Huihui; Xiao, Wei; Chen, Wenli; Xu, Fang; Zeng, Xingruo (Frontiers in Nutrition, 2024)
The association between serum uric acid (UA) and all-cause and cardiovascular-related mortality in hemodialysis (HD) patients are conflicting. We investigated this association and explored the effect moderation of underlying nutritional status as reflected in the Lean Tissue Index (LTI) and the Geriatric Nutritional Risk Index (GNRI), which are surrogate of muscle mass and nutritional risk in HD patients.Methods: A retrospective cohort study was conducted from January 2019 to December 2023. We investigate the association between serum UA and outcomes by using the Cox proportional hazards regression and restricted cubic spline function. Subgroup analyses based on LTI and GNRI were conducted to explore possible effect modifications.Results: During a mean of 32.9 months of follow-up, 876 patients treated with HD were included. The association between serum UA and all-cause mortality showed a non-linear U-shaped pattern (P = 0.007), with a survival benefit for serum UA levels between 3.4 and 6.8 mg/dl. In the multivariable-adjusted model, the low and high UA group was associated with greater risk of all-cause mortality compared to the reference UA group (HR=1.24, CI 1.03-2.12, P=0.027; HR=1.09; CI 1.05-2.08. P=0.012). In low UA group, the greater risk of mortality was observed with low LTI (<12.3; HR 1.56, 95% CI 1.22-1.82) and GNRI (<102.1; HR 1.43, 95% CI 1.12-1.76), but not with high LTI and GNRI. There seems no significant association between serum UA and cardiovascular disease-related mortality.Our study shows that lower or higher serum UA levels increase the risk of all-cause mortality in HD patients. Among patients with lower UA levels, low LTI and GNRI showed a greater risk of mortality. It suggested that a better nutritional status and not elevated UA levels is likely to improve long-term survival in HD patients.